Visual Modulation of Human Responses to Support Surface Translation - Akçay, Mustafa Emre; Lippi, Vittorio; Mergner, Thomas (Frontiers in Human Neuroscience, 2021)
Vision is known to improve human postural responses to external perturbations. This study investigates the role of vision for the responses to continuous pseudorandom support surface translations in the body sagittal plane in three visual conditions: with the eyes closed (EC), in stroboscopic illumination (EO/SI; only visual velocity information) and with eyes open in continuous illumination (EO/CI; position and velocity information). In the frequency spectrum of the translation stimulus we distinguished on the basis of the response patterns between a low-frequency, mid-frequency, and high-frequency range (LFR: 0.0165-0.14 Hz; MFR: 0.15-0.57 Hz; HFR: 0.58–2.46 Hz). With EC, subjects’ mean sway response gain was very low in the LFR. It increased with EO/SI and more so with EO/CI (p=0.078, p<10-6, respectively). In contrast, the gain in the MFR decreased from EC to EO/SI and further to EO/CI (p=0.548, p=0.0002). In the HFR, all three visual conditions produced similarly high gain levels. A single inverted pendulum (SIP) model controlling center of mass (COM) balancing about the ankle joints formally described the EC response as being strongly shaped by a resonance phenomenon arising primarily from the control’s proprioceptive feedback loop. The effect of adding visual information in these simulations lies in a reduction of the resonance, similar as in the experiments. Extending the model to a double inverted pendulum (DIP) suggested in addition a biomechanical damping effective from trunk sway in the hip joints on the resonance.